Behavior of Structural Concrete Frames with Hybrid Reinforcement under Cyclic Loading - Asmaa Sobhy; Louay Aboul Nour; Hilal Hassan; Alaaeldin Elsisi (Fracture and Structural Integrity)
A substantial amount of work was carried out on the use of fiber-reinforced polymer (FRP) in reinforcing concrete structural elements, which demonstrated considerable inelasticity or deformity through monotonous and fatigue loads. Even so, the action of FRP bars in FRP-RC columns and frame structures has not yet been studied during reversed cyclic loading.